I love hugs - Jones, Lara. (New York : Scholastic Inc., 2001)
"I love hugs...bear hugs, make-it-better hugs, and especially good-night-sleep-tight hugs. A charming book about all kinds of hugs for toddlers everywhere!"
Board books.
Cover title.
"Cartwheel books."
Keywords: Hugging -- Fiction